TELEVISION AND DEMOCRACY. A STUDY ON THE SOCIO-HISTORICAL ROADCAST AND ITS OFFERINGS IN MEXICO CITY (Andamios, Revista de Investigación Social, 2010)
This paper analyzes the program offerings on broadcast television in Mexico City from its own content and from a structural perspective in three dimensions: socio-historical, economic and political, to reflect on their implications for the transition to democracy. In that sense realize the results of a socio-historical analysis of broadcast television in Mexico City, a review of communications policies in the Mexican television derived from the historical relationship between media-state and program offerings in open signal. The paper reports a high concentration in two major television companies and resulting in a very limited supply of content to the production of six stations, two with high prevalence and important guidance to the entertainment and fiction, one that reproduces the model above, and three of the so-called “public” with a marginal line, as the choice for the metropolitan audience.
Keywords: Broadcasting; television programming; communication policy; relationship media-state democracy